Comparison of Secretome Profile of Pathogenic and Non‐Pathogenic Entamoeba histolytica. Issue 7 (7th March 2018) - Ahn, Chun‐Seob; Kim, Jeong‐Geun; Shin, Myeong Heon; Lee, Young Ah; Kong, Yoon
Abstract: The obligatory intracellular protozoan parasite Entamoeba histolytica causes amebic dysentery and liver abscess. E. histolytica adheres to the host tissues in a contact‐dependent manner. E. histolytica excretory–secretory products (ESP) might play critical roles during invasion. We comparatively analyzed the secretome profile of E. histolytica pathogenic HM‐1:IMSS and non‐pathogenic Rahman strains. The two ESP revealed similar but distinct spotting patterns. In both ESP, alcohol dehydrogenase, enolase 1, and transketolase, which control classical carbohydrate metabolism and other moonlighting effects, constituted the most abundant fractions. We recognized differently secreted molecules. Secretion of cytoskeletal organization proteins (actin, actin binding protein, and EHI_068510), protein remodeling amino peptidase, and multifunctional elongation factor 1‐α were increased in Rahman. Conversely, carbohydrate metabolizing enolase 1, alcohol dehydrogenase, transketolase, calponin, phosphoglucose mutase, malic enzyme and EHI_156420, xenobiotic scavenging superoxide dismutase and EHI_140740, and pyruvate:ferredoxin oxidoreductase and coronin (carbohydrate metabolism/detoxification) showed reduced secretion. Transcription levels of some genes involved in these processes also decreased. Changes of secretory behavior, especially decreased secretion of multifunctional carbohydrate metabolizing enzymes and detoxifying proteins that importantly participated in amoeba pathogenesis might reflect avirulent nature of Rahman strain in the host.